Career mobility of temporary workers within and across establishments: A demand-side perspective - Philipp Grunau; Christian Hohendanner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper addresses the career mobility of temporary workers from a demand-side perspective, focussing on promotions to managerial positions and wage growth. We use a large-scale revised administrative data source on employees entailing the entire population of promotions, which are considered a rare event. We provide evidence that compared to employees with a permanent contract, temporary workers are more likely to be promoted to a managerial position. Looking closer, this advantage is more pronounced across than within establishments, which we interpret as evidence for the greater importance of the flexibility over the screening function of temporary employment. However, because the qualification-related impact of fixed-term contracts on promotion is U-shaped, i.e. lowest for the medium-skilled IVET workers with long training periods in the establishments, we conclude that the screening function is still relevant in the German labour market. Moreover, the wage growth premium we find to be associated with fixed-term contracts can be explained by the fact that temporary workers benefit more from promotions to managerial positions. [166 words]
Keywords: M51; J41; J62; 330